Challenging conventional wisdom on illicit economies and rural development in Latin America. (October 2022) - Sauls, Laura Aileen; Dest, Anthony; McSweeney, Kendra
Highlights: Problematizes conventional arguments of state absence as a key problem for rural communities affected by illicit economies. Traces how illicit and licit economies intertwine and contribute to state formation processes, including in historically marginalized areas. Highlights the importance of ethnographic and mixed methods research for studying the illicit. Proposes that broader transformations in policy, politics, and dominant economic narratives are required to enable rural development. Abstract: Illicit economies have become a major driver of socio-environmental change in Latin America's rural spaces. The arrival of transnational drug trade networks in rural communities has significantly altered the economic, political, and social dynamics of entire regions. The drug trade has particularly affected the ancestral territories of Indigenous and Afro-descendent peoples, which coincide with significant areas of forests and high biodiversity, increasingly making trafficking an issue of racial and environmental justice as well. Furthermore, the decades-long drug wars, sponsored in large part by the United States Government, have fundamentally altered economic, social, environmental, and political conditions in areas of production and transshipment. The convergence of competing claims on rural spaces coupled with the violence provoked by the drug trade and state reactions to it enable and constrain possibilities for transformative action on the part of rural communities, and for development and governance projects. In this introduction to the Special Issue, we provide an overview of cross-cutting insights and key conceptual and methodological themes from the nine included papers. These findings challenge normative narratives of how illicit economies negatively affect political stability and economic development, problematizing especially the role of the state and market economies in this nexus. These papers also make clear the importance of mixed methods and ethnographic research that attends to questions of power to describe, explain, and transform illicit economies' roles in this dynamic region.